KEPEMIMPINAN PEREMPUAN DALAM PENDIDIKAN ISLAM: PELUANG, TANTANGAN, DAN KONTRIBUSINYA TERHADAP PENINGKATAN MUTU PENDIDIKAN - Yetri; junaidi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Women's leadership in Islamic education has become an increasingly important issue due to the growing participation of women in various sectors, including education. This study aims to examine the concept of women's leadership from an Islamic perspective, analyze the opportunities and challenges faced by women in leading Islamic educational institutions, and identify their contributions to improving educational quality. This study employs a library research method with a qualitative descriptive approach. Data were collected from scientific literature, including books, journals, articles, and relevant documents. The findings reveal that Islam provides broad opportunities for women to participate in leadership roles as long as they possess adequate competence, integrity, and capabilities. Women's leadership contributes positively to the development of a humanistic organizational culture, improvement of learning quality, strengthening character education, and creating inclusive educational environments. However, women still face challenges such as patriarchal culture, gender stereotypes, and dual responsibilities in domestic and professional spheres. Therefore, support from various stakeholders is essential to strengthen women's capacity in Islamic educational leadership